The implementation Project-Based Learning in lower secondary school: a critical review - Darmilah, Siti; Rochintaniawati, Diana; Rafikah Agustin, Rika (Research in Physics Education, 2023)
The learning that is widely recommended to improve science skills is project-based learning. Several studies show that the application of project-based learning models or methods or learning strategies increases motivation, achievement, problem-solving abilities, and so on. However, in reality, in the field, teachers have difficulty adopting project-based learning in schools, because several supporting factors are inadequate. Supporting factors for the success of project-based learning include a comprehensive curriculum, learning environment, appropriate assessment, student self-efficacy and support from stakeholders, especially parents. This critical review study reviews how research on project-based learning produces learning outcomes according to Project-based learning standards. In the initial stage, the author looked for as many articles as possible regarding project-based learning, especially in the science field, provided the articles were reputable. Then, reputable articles are selected that are appropriate to the implementation of project-based learning. The results of the critical review study show three important points in implementing Project-based learning to be more successful, namely: comprehensive curriculum support; the approach widely used in Project-based learning is STEM; and the implementation of Project-based learning must be adapted to suit the characteristics of students.